Tunisia : 2004 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Tunisia. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation states that the strength of the Tunisian economy continued in 2003, and the short-term outlook is favorable. Favorable agricultural production and robust nonenergy exports contributed to high growth and a narrowing of the external current account deficit in 2003. Monetary policy remains prudent and inflation under control. Greater exchange rate flexibility and the appreciation of the euro vis-a-vis the United State dollar have led to a depreciation of the dinar in real effective terms.